Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1243/09544054jem1321
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on springback/negative springback phenomena using finite element method and experimental approach

Abstract: In sheet metal forming processes, one of the main problems is the occurrence of springback/negative springback which can be influenced by various factors. A number of research scientists have conducted valuable investigation on springback phenomenon. However, the negative springback problem has rarely been investigated. In this study, the effect of geometric and non-geometric parameters such as sheet thickness, sheet anisotropy, and punch tip radius on the springback/negative springback phenomena was investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…The measured radius is the final radius after the springback. The springback in sheet metal forming has already been investigated in several studies including references [20], [22], and [23]. It can be estimated from [20,22] …”
Section: Methodsmentioning
confidence: 99%
“…The measured radius is the final radius after the springback. The springback in sheet metal forming has already been investigated in several studies including references [20], [22], and [23]. It can be estimated from [20,22] …”
Section: Methodsmentioning
confidence: 99%
“…If R tj and R cj , as shown in Figure 4, are the radii in which the jth layer yields in tensile and compressive stresses, respectively, they can be calculated using equations (12) and (13) …”
Section: Primary Bending Theorymentioning
confidence: 99%
“…They studied the effect of punch radius, sheet thickness and sheet orientation corresponding to the rolling direction on the springback and spring forward in V-bending process. 12 Mori et al investigated the springback of the ultra light steel in V-die bending controlled with a computer numerical control (CNC) servo press. The effect of the final sheet reduction in bottoming, forming speed and holding time at the end of the forming was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Behrouzi et al 11 applied bending theory in an inverse algorithm for springback compensation in V-bending of sheets. Rahmani et al 12 examined effects of sheet thickness and bending orientation with respect to the rolling direction (RD) on springback in V-bending of steel sheets. It was shown that by increasing bending orientation, yield strength and springback increased.…”
Section: Introductionmentioning
confidence: 99%